Development of a nested real time PCR/high resolution melting assay for human T‐cell lymphotropic viruses types 1 and 2 (HTLV‐1 and 2) identification. (9th June 2022) - Caputo, Mariela; Trinks, Julieta; Azcurra, Marcela; Corach, Daniel
Abstract: HTLV‐1 and HTLV‐2 are present in different high‐risk populations, such as sexual workers and injecting drug users (IDUs). HTLV‐1 is endemic in areas of Middle East, Southern Japan and Latin America, whereas HTLV‐2 infection is endemic among some Native Americans and some Central African tribes. The pathogenic consequences and clinical manifestations of these two viruses differ significantly, demanding an adequate identification; therefore, proper diagnosis of HTLV‐1 and 2 infection is crucial. To get a final diagnosis of HTLV‐1 or 2 infection, it is recommended that positive serologic samples should be confirmed by PCR assays or western blot (WB) analysis. Thus, the aim of this study was to develop and implement a simple reaction for the rapid identification of HTLV‐1 and 2. Nested real‐time PCR technique followed by high resolution melting was performed based on the tax/rex sequences of HTLV‐1 (M2) and HTLV‐2 (MoT) cell lines perfectly discriminating between HTLV‐1 from HTLV‐2, by distinct melting curve profiles. The sensitivity assay of this method revealed that at least 1 viral copy of HTLV‐1 or 1·5 viral copy of HTLV‐2 could be amplified. Later, this method was validated using 200 blood samples from corpses. In agreement with previous epidemiological, the HTLV‐1 and 2 prevalence was 1·5% (CI 95%: 0·31–4·3) and 0·5% (CI 95%: 0·013–2·75), respectively. The strategy proposed herein has some advantages over other PCR‐based tests because it not only reduces considerably time and the costs of the total diagnosis but also allows detection and discrimination of HTLV‐1 and 2 in the same reaction. Abstract : Significance and Impact of the Study: HTLV‐1 and HTLV‐2 are present in different high‐risk populations; pathogenic consequences and clinical manifestations of these two viruses differ significantly, demanding proper diagnosis. A nested real‐time PCR technique for rapid identification of HTLV‐1 and 2 followed by high resolution melting was designed with a sensitivity assay of at least 1 viral copy of HTLV‐1 or 1·5 viral copy of HTLV‐2.